Broadband Single-layer E-Patch Reflectarray - Lee, Shin-Rou; Lim, Eng-Hock; Lo, Fook-Loong (Společnost pro radioelektronické inženýrství, 2017)
E-shaped patch resonator is proposed for designing a novel broadband linearly polarized reflectarray for the first time. The element is made up of a shorted E-shaped patch with a polystyrene foam placed beneath it, and no dielectric substrate is needed in the reflectarray design. The unit element is simulated using Floquet method and it is found that a reflection phase range of ~360° is easily obtainable by varying the arm length of the shorted E-shaped patch. A full 11 × 11 reflectarray has been designed to achieve an antenna gain of ~23.7dBi and a -1dB gain bandwidth of 8.1%. The cross-polarization is found to be ~18dBi smaller than its co-polarization in the boresight direction. The proposed reflectarray is simple to design as it requires the use of only a single layer.
Keywords: Reflectarray; shorted E-shaped patch; linearly polarized reflectarray